Singapore voices : an interactive installation about languages to (re)(dis)cover the intergenerational distance - Lindborg, PerMagnus (2011)
Singapore Voices is an interactive installation, integrating sound and image in a series of touch-sensitive displays. Each display shows the portrait of an elderly person, standing with the hand turned outwards, as if saying: "i built this nation". Two displays can be seen in Figure 1 below. When the visitor touches the hand or shoulder, they hear a recording of the speaker's voice. Chances are that the visitor will not be able to understand the language spoken, but she or he will indeed grasp much of all that is, in a manner of speaking,"outside" of the words - elements of prosody such as phrasing and speech rhythm, but also voice colour that may hint at the emotional state of the person. Then there is coughing, laughing, a hand clap and so forth. Such para lingual elements of vocal communication are extremely important and furthermore, their meaning is quite universal.